OPTIMALISASI FEED RATE DAN DEPTH OF CUT CNC TURNING LEADWELL LTC-200 TERHADAP KEKASARAN PERMUKAAN ALUMINIUM SERI 6061 ALUMINUM: OPTIMIZATION OF FEED RATE AND DEPTH OF CUT OF CNC TURNING LEADWELL LTC-200 AGAINST SURFACE ROUGHNESS OF 6061 SERIES - Thoifur, Muhammad (Jurnal Teknik Mesin, 2024)
Along with the rapid development of the times. Many technologies make it easier for humans in daily life and work. One of them is in the manufacturing industry, the machining process is very important for the production process. To produce good product quality, the machining process using CNC lathe is a solution for high accuracy and efficient workmanship, especially for production processes that use lathes. There are several factors that affect the roughness value of a production result such as cutting speed, feed rate, depth of cut. The data collection process is carried out using the factorial DOE method to determine the combination of factors and levels. After machining is completed, the surface roughness of the 6061 aluminum specimen is measured using a surface roughness tester. The results of the study showed that the optimal combination of feed rate and depth of cut in the Leadwell LTC-200 CNC turning process in producing low surface roughness was at a feed rate of 0.05 mm/rev and a depth of cut of 0.2 mm with an average surface roughness value of 0.352 µm. or equivalent to N5.